Exploring experiences of heterosexism and coping strategies among lesbian, gay, bisexual, and transgender persons in Swaziland. Issue 1 (2nd January 2018) - Logie, Carmen H.; Perez-Brumer, Amaya; Woolley, Emma; Madau, Veli; Nhlengethwa, Winnie; Newman, Peter A.; Baral, Stefan D.
ABSTRACT: Social, cultural, and institutional processes which see heterosexuality as natural and universal discriminate against individuals who differ from this norm. This article draws on interviews with lesbian, gay, bisexual, and transgender (LGBT) people in Swaziland to provide an enhanced understanding of the ways in which heterosexism operates in practice and impacts the sexual rights of LGBT communities in Swaziland, where same-sex practices are criminalised. These narratives show the importance of solidarity and activism in coping strategies to challenge social exclusion, improve lives, and advocate for social changes. These strategies include reframing, navigating interpersonal relationships, and advocacy. We consider key lessons that emerge from our research for policy, programmes, and activism in Swaziland, as well as other low- and middle-income contexts.